Prevalence of Wheezing and Associated Risk Factors Among Infants in Recife, Pernambuco State, Brazil [Prevalência de Sibilância E Fatores de Risco Associados Em Crianças No Primeiro Ano de Vida, Residentes No Município de Recife, Pernambuco, Brasil] - Mallol-Villablanca, E (2011)
Sin Editorial Disponible